The clinical impact of artemisinin resistance in southeast Asia and the potential for future spread - Woodrow, C; White, N (Oxford University Press, 2017)
Artemisinins are the most rapidly acting of currently available antimalarial drugs. Artesunate has become the treatment of choice for severe malaria and artemisinin-based combination therapies (ACTs) are the foundation of modern falciparum malaria treatment globally. Their safety and tolerability profile is excellent. Unfortunately P. falciparuminfections with mutations in the ‘K13’ gene, with reduced ring-stage susceptibility to artemisinins, and slowparasite clearance in patients treated with ACTs, are now widespread in southeast Asia. We review clinical efficacy data from the region (2000-2015) that provides strong evidence that the loss of first-lineACTs in western Cambodia, first artesunate-mefloquine and then DHA-piperaquine, can be attributed primarily to K13 mutated parasites. The ring-stage activity of artemisinins is therefore critical for the sustained efficacy of ACTs; once it is lost, rapid selection of partner drug resistance, and ACT failure, are inevitable consequences. Consensus methods for monitoring artemisinin resistance are now available. Despite increased investment in regional control activities, ACTs are failing across an expanding area of the Greater Mekong subregion. Although multiple K13 mutations have arisen independently, successful multi-drug resistant parasite genotypes are taking overand threaten to spread to India and Africa. Stronger containment efforts and new approaches to sustaining long-term efficacy of antimalarial regimens are needed to prevent a global malaria emergency.